Study on the performance of base-isolated structures against progressive collapse and parametric analysis - Ma, Xiaotong; Bao, Chao; Wang, Huxiang; Long, Huan; Peng, Luyuan; Lim, Kar Sing (Structures (Oxford), 2025)
Seismic isolation structures offer significant advantages in resisting seismic hazards. However, due to their unique structural form, the research findings on progressive collapse resistance for traditional seismic structures are not entirely applicable, and these structures still face the potential risk of progressive collapse. This study focuses on the investigation of base isolated structures, utilizing a combination of experimental and simulation analysis to systematically explore the mechanism of progressive collapse resistance in base-isolated structures. The goal is to provide a scientific foundation for assessing the progressive collapse resistance of these structures. Based on the experimental data, the effects of different factors on the progressive collapse resistance were thoroughly analyzed. The study reveals the following key findings: enhancing the horizontal stiffness of the seismic isolation layer and increasing the size of the isolation beams effectively improves the collapse load-carrying capacity; improving concrete strength has a limited effect on the remaining structural load-carrying capacity; the failure modes of the inner and side column bearings are symmetrically distributed, with the remaining structural resistance of the side column bearings significantly lower than that of the inner columns due to a lack of constraints. Furthermore, the corner column bearings exhibit the lowest load-carrying capacity when the corner columns fail. Therefore, measures must be taken to improve the progressive collapse resistance of base-isolated structures.